2014
DOI: 10.1111/1469-0691.12221
|View full text |Cite
|
Sign up to set email alerts
|

Does a rapid diagnosis of Clostridium difficile infection impact on quality of patient management?

Abstract: A rapid and accurate diagnosis of Clostridium difficile infection (CDI) is essential for patient management and implementation of infection control measures. During a prospective time-series study, we compared the impact of three different diagnostic strategies on patient care. Each strategy was tested during a 3-month period: P1 (diagnosis based on the stool cytotoxicity assay and the toxigenic culture), P2 (diagnosis based on PCR) and P3 (two-step algorithm based on glutamate dehydrogenase detection followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…The small rate of less than 8% for contact between a confirmed case of CDI and other patients concurs to the idea that the rapid implementation of isolation measures has a beneficial role against spreading of the disease, controlling the transmission of C. difficile [30]. We stress on the significance of low threshold for CD testing in a surgical unit, providing an early diagnostic with excellent results in CD eradication, mortality and morbidity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The small rate of less than 8% for contact between a confirmed case of CDI and other patients concurs to the idea that the rapid implementation of isolation measures has a beneficial role against spreading of the disease, controlling the transmission of C. difficile [30]. We stress on the significance of low threshold for CD testing in a surgical unit, providing an early diagnostic with excellent results in CD eradication, mortality and morbidity.…”
Section: Discussionsupporting
confidence: 76%
“…We need to take into account that the median stay in the oncology clinic is only 3 days. It is statistically proven that hospital stays longer than 10 days increase the risk of exposure and a transfer from a medical ward is a significant parameter for CDI [10].The small rate of less than 8% for contact between a confirmed case of CDI and other patients concurs to the idea that the rapid implementation of isolation measures has a beneficial role against spreading of the disease, controlling the transmission of C. difficile [30]. We stress on the significance of low threshold for CD testing in a surgical unit, providing an early diagnostic with excellent results in CD eradication, mortality and morbidity.…”
mentioning
confidence: 92%
“…13 reducing delays in testing may improve the quality of patient management [40]. Several recent studies have demonstrated that real-time PCR for toxin B gene has a high sensitivity and specificity in detecting CDI [7,10].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…One recent study shows that the number of unnecessary days of contact precaution and unjustified antibiotic usage decreased by nearly 40% for those patients who were diagnosed as negative for CDI by molecular testing compared to those diagnosed with CCNA or enhanced cell culture. The same study showed that the use of molecular testing decreased the length of hospitalization on average by more than 7 days compared to that for CCNA or enhanced cell culture (6).…”
mentioning
confidence: 88%
“…The increased economic burden in hospitalized patients due to CDI has been estimated at $9,822 to $13,854 per patient, and total patient costs (health care costs plus lost wages) associated with CDI have been estimated to exceed $1 billion annually in the United States alone (3,4). Several recent studies have demonstrated that rapid and accurate detection of C. difficile is an important component of combating hospital-acquired CDI and can have a significant benefit to patients and hospitals from a financial and clinical perspective (4)(5)(6).…”
mentioning
confidence: 99%